STRATEGI BISNIS DALAM MENINGKATKAN KINERJA BISNIS RUMAH MAKAN DI KALIMANTAN TENGAH - Fiasco Darung; Vivy Kristinae (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Management research is aimed at the restaurant business for survival by following the government regulations of the COVID-19 period and exploring knowledge in applying business change methods. The purpose of this research is to improve business performance in a pandemic by sharing knowledge to obtain product marketing information, building cooperation in activities that significantly improve business performance when the economy is weak. Quality products made hygienically with the best raw materials, processing, packaging and shipping have very positive business performance. Quantitative research methods with SPSS 23.0 from distributing questionnaires to 150 restaurant entrepreneurs in Central Kalimantan. The results showed the effect of sharing knowledge and 72.9% product quality on the performance of technology-based restaurant businesses during the pandemic. The implications of this study are aimed at restaurant operators in Central Kalimantan in particular and the restaurant business in other provinces in general, to utilize technology to build relationships in sharing information and maintaining customer confidence in quality products.